Energy absorption of circular honeycomb out-of-plane dynamic impact under oblique loading - Sze Pei, Tan; Siti Nadiah, Mohd Saffe; Siti Aishah, Rusdan (Centre for Advanced Research on Energy (CARe), 2019)
This paper presents the circular honeycomb filler subjected to oblique loading (